Widespread Contamination by Anticoagulant Rodenticides in Insectivorous Wildlife from the Canary Islands: Exploring Alternative Routes of Exposure - Beatriz Martín Cruz; Andrea Acosta Dacal; Ana Macías-Montes; Cristian Rial-Berriel; Manuel Zumbado; Luis Alberto Henríquez-Hernández; Ramón Gallo-Barneto; Miguel Ángel Cabrera-Pérez; Octavio P. Luzardo (Toxics)
Research on anticoagulant rodenticides (ARs) in wildlife has primarily focused on apex predators, with less attention given to their potential integration into lower trophic levels and the associated exposure pathways. At the base of the terrestrial food web, invertebrates have been suggested as potential vectors of ARs to insectivorous species such as small mammals, reptiles, and birds. To explore this hypothesis, we analyzed the presence of nine anticoagulant rodenticides—including both first-generation (FGARs) and second-generation (SGARs) rodenticides—in 36 liver samples from Yemen chameleons (Chamaeleo calyptratus) and 98 liver samples from six non-raptorial, predominantly insectivorous bird species from the Canary Islands. Through HPLC-MS/MS analysis, only SGARs were detected in both animal groups collected between 2021 and 2024. Approximately 80% of reptiles and 40% of birds tested positive for at least one SGAR, with brodifacoum being the most frequently detected compound. In more than 90% of positive cases, it was found as the sole contaminant, while co-occurrence with other SGARs was uncommon. Additionally, most concentrations were below 50 ng/g wet weight, except for two bird specimens, suggesting heterogeneous exposure scenarios and potential variability in contamination sources across individuals. These findings provide evidence of AR integration at the base of the terrestrial food web in the Canary Islands and suggest secondary exposure via invertebrates as a plausible route of contamination. Further research directly analyzing invertebrate samples is needed to confirm their role as vectors of ARs to insectivorous wildlife in insular ecosystems.